SCHOOL INSPECTORS GUIDANCE ON TEACHER'S EDUCATION FROM 1970 TO 1976: A LOOK OVER SAO PAULO - Leite Barbosa, Raquel Lazzari [UNESP]; Nicacio, Rosemary Trabold (Unesp-faculdade Ciencias & Letras, 2021)
This article discusses isolated school teachers' training practices in Assis-Sao Paulo state from 1970 to 1976. That education was led by school inspectors with the help of state Pedagogical Guidance Service. This is a documental research with transnational approach concerning education history which analyzed teachers' education practices through speeches registered in pedagogical meeting minute. The inspectors were responsible for guiding and supervise the syllabus whose implementation would increase education quality in the state by eliminating grade failure in primary schools and meet the guidelines enforced by an economic development program signed up between Brazil and the United States of America.
Keywords: Teachers' education; School inspectors; Elementary schooling; SEROP (Pedagogical Guidance Service in Portuguese); Isolated schools